2006
DOI: 10.1073/pnas.0505407103
|View full text |Cite
|
Sign up to set email alerts
|

Elevated cholecystokininergic tone constitutes an important molecular/neuronal mechanism for the expression of anxiety in the mouse

Abstract: Cholecystokinin (CCK), one of the most abundant neuropeptides in the brain, plays an important role in anxiogenesis through the activation of CCK receptor-2 (CCKR-2). Accumulating evidence, however, has suggested this role depends on endogenous CCKergic ''tone,'' which is largely determined by the expression level of the CCKR-2. Using the tTA͞tetO-inducible transgenic (tg) approach, we show here that overexpression of the CCKR-2 in neurons of the forebrain significantly increases CCKR-2 binding capacity in tg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 59 publications
2
33
0
Order By: Relevance
“…1A). The expression pattern of the CCKR-2 transgene (data not shown) was the same as both the pattern of the tTA expression and the CCKR-2 transgene expression reported in our previous study [101]. …”
Section: Expression Of the Cckr-2 Transgene In The Brain Of Dtg Micesupporting
confidence: 51%
See 3 more Smart Citations
“…1A). The expression pattern of the CCKR-2 transgene (data not shown) was the same as both the pattern of the tTA expression and the CCKR-2 transgene expression reported in our previous study [101]. …”
Section: Expression Of the Cckr-2 Transgene In The Brain Of Dtg Micesupporting
confidence: 51%
“…Virtually, the CCKergic system has long been recognized as an anxiogenic factor for the animals [98], and this effect has been well validated in human populations as well [89,99,100]. Our recent study also showed that overexpression of CCKR2 in neurons of the forebrain of mice significantly enhanced ALBs [101]. At the same time, some candidate genes that are linked to ADs are also associated with HPA axis activity.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…The CCKA receptor (recently termed CCK-1R) is expressed at relatively low levels, while the CCKB receptor (or CCK-2R) is densely distributed in the forebrain regions. There is general agreement about the influence of CCK-2R in generating anxiety-like behaviors and emotional responsiveness (Bradwejn et al, 1991;Van Megen, 1996;Farook et al, 2001;Chen et al, 2006). However, the anxiolytic profile of CCK-2R antagonists has been questioned (Griebel, 1999) thus raising serious concerns about the therapeutic potential of targeting the CCK system (Abelson, 1995).…”
Section: Introductionmentioning
confidence: 99%